Predictors of rapid high weight gain in schizophrenia: Longitudinal analysis of the French FACE-SZ cohort. (November 2017) - ,; Andrianarisoa, M.; Aouizerate, B.; Berna, F.; Blanc, O.; Brunel, L.; Bulzacka, E.; Capdevielle, D.; Chereau-Boudet, I.; Chesnoy-Servanin, G.; Danion, J.M.; D'Amato, T.; et al.
Abstract: Metabolic syndrome (MetS) is highly prevalent in schizophrenia. However very little is known about the time course of MetS and its components. The few longitudinal studies that have been carried out had small sample sizes and a short follow-up. The aim of our study was to evaluate the prevalence of MetS and its components, at baseline and one year later, and to investigate predictors of weight gain (WG) in a cohort of individuals with schizophrenia. We followed 167 schizophrenia patients from the FACE-SZ cohort for one year. The Structured Clinical Interview for DSM-IV (SCID) was used to confirm the diagnosis of schizophrenia. Data on socio-demographic and clinical characteristics, antipsychotic treatment, and comorbidities were collected, and a blood sample was drawn. We found that the prevalence of MetS increased from 21.0% to 26.6% after one year. Patients with baseline depressive symptoms had a 4.5-fold higher risk of WG at the one-year follow-up (p = 0.02) than those without depressive symptoms, after adjusting for confounding variables. WG also correlated with high levels of metabolic parameters and peripheral inflammation. These findings highlight the need to systematically diagnose depression in Schizophrenia. Future studies should determine whether specific pharmacological and non-pharmacological interventions for depression in SZ subjects are effective in preventing rapid high weight gain. Highlights: MetS prevalence and its component significantly increased in a short time period of one year in individuals suffering from Schizophrenia. Depression is the strongest predictor of rapid weight gain at one year and should be systematically diagnosed and treated in all weight-targeted interventions. Comprehensive evaluation and personalized recommendation are not sufficient in limiting MetS onset in SZ patients.